A Rapid Seismic Risk Assessment Method for Existing Building Stock in Urban Areas. (2015) - Albayrak, Uğur; Canbaz, Mehmet; Albayrak, Gülçağ
Abstract: Eskisehir is a city in the northwestern part of Turkey which is seismically quite active zone. For this reason, identifying and strengthening of the deficient buildings in northern part of Eskisehir city center is very important in terms of minimal loss of life and damage. The proposed methodology for seismic failure risk assessment in urban building stock is based on the techniques of the screening procedure developed by Sucuoğlu. Rapid street screening for potential seismic hazards is a simple and effective seismic risk assessment method. The procedure is applied to detect, inventory, and rank the most vulnerable buildings in specified region that may damage during a forthcoming earthquake. Applied method is based on the observations and giving score for the selected buildings, considering some selected parameters from the street walking. The risk assessment considered criteria as the age of building, number of stories, existence of soft story, short column, heavy overhangs, pounding affect, topographic effects, visual building construction quality and earthquake zone where the building was located. After the first step evaluation on site, determined performance score (Earthquake Risk Score–E.R.S) of each building was calculated and the most dangerous buildings in terms of earthquake safety were identified. In a large scale in-situ investigation a set of 1643 buildings within the northern part of Eskisehir were seismically assessed. According to the E.R.S. points, each inspected building was classified into one of three vulnerability classes which are high risk, moderate risk and low risk. The results revealed that total 218 among 1643 buildings were classified as high risk and more detailed evaluations of these buildings were recommended before confirming the building as earthquake risk.